Forbidden hugs in pandemic times III. Observations of the luminous red nova AT 2021biy in the nearby galaxy NGC 4631 - Cai Y.-Z.; Pastorello A.; Fraser M.; Wang X.-F.; Filippenko A. V.; Reguitti A.; Patra K. C.; Goranskij V. P.; Barsukova E. A.; Brink T. G.; Elias-Rosa N.; Stevance H. F.; et al. (EDP SCIENCES S A, 2022)
We present an observational study of the luminous red nova (LRN) AT 2021biy in the nearby galaxy NGC 4631. The field of the object was routinely imaged during the pre-eruptive stage by synoptic surveys, but the transient was detected only at a few epochs from ∼231 days before maximum brightness. The LRN outburst was monitored with unprecedented cadence both photometrically and spectroscopically. AT 2021biy shows a short-duration blue peak, with a bolometric luminosity of ∼1.6 × 1041 erg s−1, followed by the longest plateau among LRNe to date, with a duration of 210 days. A late-time hump in the light curve was also observed, possibly produced by a shell-shell collision. AT 2021biy exhibits the typical spectral evolution of LRNe. Early-time spectra are characterised by a blue continuum and prominent H emission lines. Then, the continuum becomes redder, resembling that of a K-type star with a forest of metal absorption lines during the plateau phase. Finally, late-time spectra show a very red continuum (TBB ≈ 2050 K) with molecular features (e.g., TiO) resembling those of M-type stars. Spectropolarimetric analysis indicates that AT 2021biy has local dust properties similar to those of V838 Mon in the Milky Way Galaxy. Inspection of archival Hubble Space Telescope data taken on 2003 August 3 reveals a ∼20 M⊙ progenitor candidate with log (L/L⊙) = 5.0 dex and Teff = 5900 K at solar metallicity. The above luminosity and colour match those of a luminous yellow supergiant. Most likely, this source is a close binary, with a 17–24 M⊙ primary component.